Modern Local Government - Janice Morphet (SAGE Publications Ltd, 2008)
The pace and scale of reform in local government always seems unremitting to those close to it. For a long period before 1997, the reforms all appeared to be focused on reducing the power and central role of local authorities, both in their democratic leadership of their communities and in being the first point of contact between citizens and government. The changes since 1997 have seen more reforms but, 10 years on, these are seen to be leading somewhere, stages on a journey that could take local government back to a point of local leadership, co-ordination, and direction. In their individual ways these reforms are frequently difficult to understand, and each has a life cycle that initially seems to introduce a very demanding target, which, after incorporation, provides the platform for the next stage of change. As a result of their response to this unremitting change, local authorities are now seen to be leaders of cultural transformation and improvement in the public sector. Local authorities still have much to do but are more confident about how to set about change and how to assess its impact on people’s lives